2014
DOI: 10.3892/br.2014.274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pertussis toxin on calcium influx in three contraction models

Abstract: Abstract. Pertussis toxin (PTX) blocks G protein activation and inhibits signal transmission from the activated receptor to effectors that are specific for the G protein-coupled receptor. The aim of the present study was to evaluate the effect of PTX on vascular smooth muscle cells that were stimulated pharmacologically with phenylephrine (α-adrenoceptor agonist), mastoparan-7 (direct G-protein activator) and Bay K8644 (direct calcium channel activator). The changes in perfusion pressure that were proportional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Our previous studies confirmed that mastoparan-7 is able to increase the calcium load in smooth muscle cytoplasm by activation of calcium influx from intra and extracellular calcium stores in an isolated resistant artery model (20,21). In addition, during ischemia and reperfusion, the pathway associated with direct stimulation of G-proteins remains active (22).…”
Section: Modulatory Effect Of Laser Irradiation On Mastoparan-7-inducsupporting
confidence: 71%
See 2 more Smart Citations
“…Our previous studies confirmed that mastoparan-7 is able to increase the calcium load in smooth muscle cytoplasm by activation of calcium influx from intra and extracellular calcium stores in an isolated resistant artery model (20,21). In addition, during ischemia and reperfusion, the pathway associated with direct stimulation of G-proteins remains active (22).…”
Section: Modulatory Effect Of Laser Irradiation On Mastoparan-7-inducsupporting
confidence: 71%
“…Arterial smooth muscle function has been investigated in a number of different studies, involving typical pharmacological stimulation with the use of receptor agonists including α 1 -adrenoceptors, vasopressin type 1 receptors or the L-type calcium channel (20)(21)(22)(23)(24)(25)28,29). Direct stimulation of G-proteins with mastoparan-7 was described in certain studies (20)(21)(22)29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of PLC smooth muscle leads to an increase in the concentration of IP 3 and DAG, which initiates the increase in the concentration of calcium ions in the cytoplasm as a result of the flow from the intracellular pool, and subsequently out of the extracellular pool (1,6). Non-selective inhibitors of PLC, such as edelfosine-ET-18-OCH3 (7) and U-73122 (8)(9)(10), reduce the efficiency of smooth muscle contraction by reducing the influx of calcium into the cytoplasm. In addition to receptor activation, it is possible to directly activate phospholipase C and this significantly increases the calcium ion concentration in the cytoplasm by 2,4,6-trimethyl-N- [3-(trifluoromethyl) phenyl]benzenesulfonamide (m-3M3FBS) (11,12); however, the selectivity of this action remains controversial (6,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Perfusion pressure was measured on BPR-01 and BPR-02 transducers (Experimetria Ltd.) connected to a digital recorder (Graphtec midi Logger GL820; Graphtec Corp., Yokohama, Japan). The peristaltic pump, which was used to induce arterial perfusion, was purchased from ZALIMP (Warszawa, Poland) (16,17). All reagents were purchased from Sigma-Aldrich (Merck Millipore, Darmstadt, Germany).…”
Section: Drugs and Solutionsmentioning
confidence: 99%